2009
DOI: 10.1007/978-3-642-03841-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Multicast Video Streaming in IEEE 802.11 b/g/n Testbed Environment

Abstract: Abstract. The aim of the work is to analyse capabilities and limitations of different IEEE 802.11 technologies (IEEE 802.11 b/g/n), utilized for both multicast and unicast video streaming transmissions directed to mobile devices. Our preliminary research showed that results obtained with currently popular simulation tools can be drastically different than these possible in real-world environment, so, in order to correctly evaluate performance of video streaming, a simple wireless test-bed infrastructure has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, the results obtained from simulations can be drastically different from those possible in the realworld environment [5].…”
Section: Related Workmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the results obtained from simulations can be drastically different from those possible in the realworld environment [5].…”
Section: Related Workmentioning
confidence: 83%
“…Video quality is considered acceptable when 0.1 < V QM < 0.3 and good when V QM < 0.1 [9]. For clips corresponding 978-1-4577-0681-3/11/$26.00 ©2011 IEEE 978-1-4577-0681-3/11/$26.00 ©2011 IEEE to test cases [1,4], overall VQM score is higher than overall VQM score of clips received during test cases [5,6]. Video Clips [1,16] were captured during office hours when ISM radio spectrum is very busy.…”
Section: ) Vqm (Video Quality Metric)mentioning
confidence: 99%
“…The problem of using more than one multicast channel is well discussed in [13]. They explain that broadcast and multicast frames (group of frames) may be transmitted only with rates that are listed in Basic Rate Set (BRS).…”
Section: B Wireless Network Set Up and Configurationmentioning
confidence: 99%
“…The authors tested the DirCast system with up to 12 users and concluded that DirCast is well suited for streaming media delivery. The authors of [11] investigate the applicability of the IEEE 802.11b/g/n technologies for multicast-based multimedia streaming. The evaluations are based on the mean opinion score of the evaluators.…”
Section: Related Researchmentioning
confidence: 99%